Os limites constitucionais na criação de cargos em comissão pela Administração Pública - Santos, Vitor Kleber Almeida (2017)
The objective of this paper is to investigate the nature and purpose of the positions in commission and the existence of constitutional limits applicable in the creation of these positions. The Federal Constitution of 1988 (article 37, II) establishes, as a rule, the obligation of prior approval in a public competition for investiture in public positions. However, at the same time, it excludes from this rule the appointment to positions in commission, which are those declared in a law of free appointment and dismissal, destined exclusively for the assignments of direction, leadership and advisory, and the law should reserve a percentage of these positions and career servers (Article 37, subsections II and V). This is an exception to the public procurement procedure and, as such, must comply with the exceptional circumstances laid down by the Constitution. However, many abuses are committed by setting up commission positions to serve personal and party interests, to the detriment of the public interest. In order to do so, positions in commission are created with labels of direction, leadership and advice, but with merely technical or bureaucratic attributions that do not depend on the bond of trust with the superior authority and also in excessive amounts and above the real needs of the Public Administration . Such facts have led the control bodies to act in an increasingly forceful way in the fight against these patrimonialist practices. The doctrine and jurisprudence have advanced in this matter, but there is still no clarity regarding the limits effectively imposed by the Federal Constitution for the creation of these positions, which is why we seek to understand these limits in order to contribute to the desired legal certainty in the matter and to the achievement of an increasingly efficient and democratic Public Administration